DJ type three-layer hybrid perovskite constructed by aromatic diamine as well as preparation method and application of DJ type three-layer hybrid perovskite

By introducing aromatic diamine and methylamine cations into the three-layer structure, the DJ-type three-layer hybrid perovskite material is constructed, which solves the problems of stability and performance attenuation of existing materials, and achieves high stability and excellent X-ray detection performance.

CN119751340APending Publication Date: 2025-04-04SHANXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411905393.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing RP-type organic-inorganic hybrid perovskite materials show rapid performance attenuation in device applications due to their instability to water, oxygen, etc., making it difficult to improve device stability and photoelectric performance while maintaining excellent semiconductor performance.

Method used

Aromatic bisamine is used to introduce strong π-π interactions into the three-layer structure, and methylamine cations are introduced through synthesis method to construct DJ-type three-layer hybrid perovskite materials to enhance the stability of the material and X-ray detection performance.

Benefits of technology

It realizes high stability and excellent X-ray detection performance of the material, exhibits ultra-high sensitivity, extremely low detection limit and high radiation stability, making it an ideal material for high-performance X-ray detectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751340A_ABST
    Figure CN119751340A_ABST
Patent Text Reader

Abstract

The invention discloses a DJ type three-layer hybrid perovskite material constructed by aromatic diamine and a preparation method and application thereof, and belongs to the technical field of X-ray detection. Aiming at the problem of how to simultaneously improve the stability and the photoelectric property of a device on the premise of maintaining excellent semiconductor performance of the existing RP type organic-inorganic hybrid perovskite material, in the DJ type three-layer hybrid perovskite material constructed by aromatic diamine, strong pi-pi interaction is introduced into the aromatic diamine, the stability of a system is enhanced, and the photoelectric property of the device is improved. And the three-layer structure has relatively high atomic number and relatively high density, so that the material shows excellent semiconductor performance and good X-ray attenuation capability. Due to the structural design, the material shows excellent performance in X-ray detection, the performance comprises ultrahigh sensitivity and extremely low detection limit, and meanwhile, the material has relatively high radiation stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of X-ray detection, and in particular relates to a preparation method and application of a DJ-type three-layer hybrid perovskite constructed by aromatic diamine. Background Art

[0002] In the field of photoelectric detection, organic-inorganic hybrid perovskite materials have shown great application potential in high-energy ray detectors such as X-ray detection due to their large carrier mobility, long carrier migration lifetime and large X-ray attenuation coefficient. However, the existing RP-type organic-inorganic hybrid perovskite materials show rapid performance degradation in device applications due to their instability to water, oxygen, etc. Therefore, how to improve device stability and photoelectric performance while maintaining excellent semiconductor performance is an important challenge in this field.

[0003] In contrast, in the DJ-type three-layer hybrid perovskite material constructed by aromatic diamines, the aromatic diamines introduce strong π-π interactions, which enhance the stability of the system, and the three-layer structure has a higher atomic number and a larger density, resulting in the material exhibiting excellent semiconductor properties and good X-ray attenuation capabilities. Furthermore, compared with other larger organic amine cations, methylamine ions can reduce the free energy and the degree of octahedral tilt of the inorganic skeleton, so that the constructed perovskite material has higher crystal symmetry, further improving the stability of the material and increasing the carrier migration lifetime. This structural design enables the material to exhibit excellent performance in X-ray detection, such as ultra-high sensitivity and extremely low detection limit, while having high radiation stability. Summary of the invention

[0004] The technical problem to be solved by the present invention in view of the above problems is to provide a method for preparing DJ-type three-layer hybrid perovskite constructed with aromatic diamines, which uses aromatic diamines to introduce strong π-π interactions in the three-layer structure, thereby enhancing the stability of the material and the X-ray detection performance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A DJ-type three-layer hybrid perovskite material constructed by aromatic diamine, wherein the DJ-type three-layer hybrid perovskite material constructed by aromatic diamine is a two-dimensional structure, and the molecular formula conforms to the general formula A 1 A 2 n-1 B n X 3n+1 , n = 3, where A 1 3-Aminomethylpyridinium cation 3AMPY 2+ , A 2 Methylamine cation MA + , B is Pb2+ , X is Br - , the molecular formula is: (3AMPY)(MA)2Pb3Br 10 ;(3AMPY)(MA)2Pb3Br 10 The crystalline material crystallizes in the centrosymmetric C2 / c space group, belongs to the 2 / m point group in the monoclinic system, and the unit cell parameter is a= α=90°, β=94.884(2)°, γ=90°, (3AMPY)(MA)2Pb3Br 10 The number of asymmetric units Z in the unit cell is 4, and the unit cell volume V is

[0007]

[0008] A method for preparing a DJ-type three-layer hybrid perovskite material constructed by aromatic diamines comprises the following steps:

[0009] Step (1), (3AMPY)(MA)2Pb3Br 10 Preparation of precursor solution:

[0010] Lead (II) acetate trihydrate powder is added to a hydrobromic acid solution, and then an appropriate amount of 3-aminomethylpyridine solution is added dropwise thereto. After heating to dissolve, a certain amount of methylamine hydrochloride powder is added to the solution after the solution is cooled to room temperature. After heating for reaction, a yellow clear solution is obtained, which is a saturated precursor solution;

[0011] Step (2), (3AMPY)(MA)2Pb3Br 10 Preparation of perovskite single crystals:

[0012] The saturated precursor solution is slowly cooled by programmed cooling in a sealed state until a large-sized single crystal is grown, namely (3AMPY)(MA)2Pb3Br 10 Crystalline material.

[0013] Through step-by-step synthesis, a (3AMPY)PbBr4 compound with a two-dimensional single-layer perovskite structure was first synthesized, and methylamine cations were further introduced to construct a two-dimensional multilayer hybrid perovskite. The methylamine cations were filled into the holes of the perovskite inorganic skeleton, and the number of inorganic layers can be controlled by the amount of methylamine cations in the holes. This synthesis method is conducive to the preparation of DJ-type three-layer hybrid perovskite materials constructed by aromatic diamines in this patent. Compared with RP-type hybrid perovskite materials, DJ-type hybrid perovskite materials constructed by aliphatic diamines, and DJ-type double-layer hybrid perovskites constructed by aromatic diamines reported previously, DJ-type three-layer hybrid perovskites constructed by aromatic diamines not only improve the stability of previous materials, but also help to enhance light absorption and improve carrier transport, thereby improving the performance of such materials for X-ray detection.

[0014] Furthermore, the molar ratio of methylamine hydrochloride to 3-aminomethylpyridine in step (1) is 18:1 to 20:1. A high molar ratio is conducive to the formation of a three-layer structure, while a lower molar ratio is conducive to the formation of a double-layer structure.

[0015] Furthermore, the concentrations of the methylamine hydrochloride and the 3-aminomethylpyridine in step (1) are 0.068 g / mmol and 0.108 g / mmol, respectively.

[0016] Furthermore, the mass solubility of the hydrobromic acid solution described in step (1) is 48%, and the dosage is 30-35 mL.

[0017] Furthermore, the concentration of lead (II) acetate trihydrate described in step (1) is 0.379 g / mmol, and the amount used is 5 to 8 mmol.

[0018] Furthermore, the programmed cooling method described in step (2) is programmed to cool the temperature by 0.5°C to 1°C per day, and the slow cooling time is 35 to 40 days.

[0019] Furthermore, the final temperature of the programmed cooling in step (2) is 45°C to 30°C.

[0020] Application of a DJ-type three-layer hybrid perovskite material constructed by aromatic diamine, the (3AMPY)(MA)2Pb3Br 10 The crystal material is used for low detection limit X-ray detection and is a new type of material in the field of X-ray detection. The material crystallizes in the centrosymmetric C2 / c space group, and its inorganic skeleton is composed of PbBr6 octahedrons connected by common vertices. The diprotonated 3-aminomethylpyridinium cations are arranged in parallel between the layers of the inorganic skeleton, and the methylamine cations are filled in the holes of the inorganic skeleton. The 3-aminomethylpyridinium cations are connected by NH … Br is connected to the inorganic skeleton through hydrogen bonding and introduces strong π-π interactions, which enhances the stability of the system.

[0021] Increasing the molar ratio of methylamine hydrochloride to 3-aminomethylpyridine is conducive to the formation of the three-layer crystal material in this patent. Compared with the double-layer material, in terms of synthesis, it is necessary to avoid the appearance of single-layer crystals and the existence of double-layer crystals in the reaction system. The synthesis of this material has certain technical difficulties in terms of purification. In addition, the interface defects of the crystal material should be avoided as much as possible during the synthesis to avoid affecting the transmission efficiency of electrons and holes. There are also challenging technical difficulties in reducing the interface defects in the synthesis of the three-layer structure. In terms of performance, the unique three-layer DJ-type crystal material has higher stability, higher photoelectric conversion efficiency and stronger X-ray absorption ability, thereby showing excellent optical and thermal properties, which is conducive to the use of the crystal material for low detection limit X-ray detection.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The preparation process of the crystal material of the present invention is simple and low in cost. The crystal material introduces strong π-π interaction through aromatic diamines, which enhances the structural stability. The stability in the air environment is up to nearly one year, and it has high thermal stability (thermal stability up to 558K).

[0024] 2. The crystalline material of the present invention has excellent optical properties. The optical band gap is reduced to 2.50 eV compared with the optical band gap (2.79 eV) of the (3AMPY) PbBr4 single-layer hybrid perovskite, which is more conducive to the improvement of the material's electrical conductivity and light absorption capacity.

[0025] 3. This invention is the first to apply DJ-type three-layer organic-inorganic hybrid perovskite material constructed by aromatic diamine to X-ray detection. The crystal material has an ultra-high sensitivity (3629μC Gy air -1 cm -2 , 20V), extremely low detection limit (41nGy air s -1 , 10V) and high radiation stability, making it one of the ideal materials for making high-performance X-ray detectors. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 (3AMPY)(MA)2Pb3Br 10 Structure diagram of

[0027] Figure 2 (3AMPY)(MA)2Pb3Br 10 Stability test chart of the material after being placed in the air for 350 days;

[0028] Figure 3 (3AMPY)(MA)2Pb3Br 10Thermogravimetric analysis curve of

[0029] Figure 4 (3AMPY)(MA)2Pb3Br 10 Absorption performance curve of

[0030] Figure 5 (3AMPY)(MA)2Pb3Br 10 Absorption spectrum of X-rays;

[0031] Figure 6 (3AMPY)(MA)2Pb3Br 10 Sensitivity comparison chart under different bias voltages;

[0032] Figure 7 (3AMPY)(MA)2Pb3Br 10 Detection limit for X-rays;

[0033] Figure 8 (3AMPY)(MA)2Pb3Br 10 radiation stability. DETAILED DESCRIPTION

[0034] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.

[0035] Example 1

[0036] Dissolve lead (II) acetate trihydrate (5 mmol) powder in 30 mL (48 wt%) hydrobromic acid solution, then add 0.88 mmol of 3-aminomethylpyridine solution to the solution, heat to boiling, wait for the solution to cool to room temperature, then add 16 mmol of methylamine hydrochloride powder, and heat to react to obtain a clear yellow solution. Transfer the above solution to a blue-capped bottle and gradually reduce the temperature from 65°C to 30°C in an oven at a rate of 1°C per day. After 35 days, a 2 mm thick (3AMPY)(MA)2Pb3Br 10 Large size single crystal.

[0037] Example 2

[0038] Dissolve lead (II) acetate trihydrate (8 mmol) powder in 35 mL (48 wt%) hydrobromic acid solution, then add 1 mmol of 3-aminomethylpyridine solution to the solution, heat to boiling, wait for the solution to cool to room temperature, then add 20 mmol of methylamine hydrochloride powder, and heat to react to obtain a clear yellow solution. Transfer the above solution to a blue-capped bottle and gradually reduce the temperature from 65°C to 45°C in an oven at a rate of 0.5°C per day. After 40 days, a 5 mm thick (3AMPY)(MA)2Pb3Br 10 Large size single crystal.

[0039] Example 3

[0040] (3AMPY)(MA)2Pb3Br 10 Analysis of light absorption ability of crystal materials:

[0041] The synthesized (3AMPY)(MA)2Pb3Br was characterized by UV-Vis absorption spectroscopy. 10 The crystal material was analyzed for its light absorption properties. The results showed that the absorption cutoff edge of the crystal can reach 513nm. g is ~2.50eV( Figure 4 ).

[0042] Example 4

[0043] (3AMPY)(MA)2Pb3Br 10 Analysis of X-ray absorption ability of crystal materials ( Figure 5 ):

[0044] Synthesis of organic-inorganic hybrid (3AMPY)(MA)2Pb3Br 10 Compared with the currently commercially available Si, α-Se, CdTe and all-inorganic perovskite MAPbBr3, (3AMPY)(MA)2Pb3Br 10 Crystalline materials exhibit excellent absorption capabilities for X-rays.

[0045] Example 5

[0046] (3AMPY)(MA)2Pb3Br 10 Analysis of X-ray detection capabilities of crystal materials:

[0047] Using 5 mm thick (3AMPY)(MA)2Pb3Br 10 X-ray detectors made of crystal materials have relatively high sensitivity, such as Figure 6 As shown, at bias voltages of 5V, 10V, and 20V, the sensitivities are 1241, 1946, and 3629μC Gy, respectively. air- 1 cm -2 At 10V, the minimum detection limit for X-rays is 41nGy air s -1 ( Figure 7 ), at a dose rate of 2.29 mGy air s -1 The (3AMPY)(MA)2Pb3Br 10 Crystalline materials have good radiation stability ( Figure 8 ). This result is sufficient to show that the crystal is an excellent X-ray detection material.

[0048] Performance evaluation of the present invention:

[0049] (1) Optical performance

[0050] The (3AMPY)(MA)2Pb3Br 10 The optical band gap of the material is reduced to 2.50 eV compared to the optical band gap (2.79 eV) of (3AMPY)PbBr4 single-layer hybrid perovskite, which is more conducive to improving the material's electrical conductivity and light absorption capacity.

[0051] (2) Thermal properties

[0052] The (3AMPY)(MA)2Pb3Br 10 The thermal stability of the material is as high as 558K, indicating that it has good thermal stability.

[0053] (3) X-ray detection performance

[0054] In order to test the X-ray detection performance of the crystal material, a small photodetector was assembled. The photodetector has an ultra-high sensitivity (3629μC Gy air -1 cm -2 , 20V), extremely low detection limit (41nGy air s -1 , 10V) and higher radiation stability (total X-ray dose of 1.15Gy).

[0055] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

Claims

1. A DJ-type three-layer hybrid perovskite material constructed by aromatic diamine, characterized in that: The DJ-type three-layer hybrid perovskite material constructed by the aromatic diamine is a two-dimensional structure, and the molecular formula conforms to the general formula A 1 A 2 n-1 B n X 3n+1 , n = 3, where A 1 3-Aminomethylpyridinium cation 3AMPY 2+ , A 2 Methylamine cation MA + , B is Pb 2+ , X is Br - , the molecular formula is: (3AMPY)(MA)2Pb3Br 10 ;(3AMPY)(MA)2Pb3Br 10 The crystalline material crystallizes in the centrosymmetric C2 / c space group, belonging to the 2 / m point group in the monoclinic system, with unit cell parameters of α=90°, β=94.884(2)°, γ=90°, (3AMPY)(MA)2Pb3Br 10 The number of asymmetric units Z in the unit cell is 4, and the unit cell volume V is 2. A method for preparing a DJ-type three-layer hybrid perovskite material constructed by aromatic diamines as claimed in claim 1, characterized in that: The steps include: Step (1), (3AMPY)(MA)2Pb3Br 10 Preparation of precursor solution: Lead (II) acetate trihydrate powder is added to a hydrobromic acid solution, and then an appropriate amount of 3-aminomethylpyridine solution is added dropwise thereto. After heating to dissolve, a certain amount of methylamine hydrochloride powder is added to the solution after the solution is cooled to room temperature. After heating for reaction, a yellow clear solution is obtained, which is a saturated precursor solution; Step (2), (3AMPY)(MA)2Pb3Br 10 Preparation of perovskite single crystals: The saturated precursor solution is slowly cooled by programmed cooling in a sealed state until a large-sized single crystal is grown, namely (3AMPY)(MA)2Pb3Br 10 Crystalline material.

3. The method for preparing a DJ-type three-layer hybrid perovskite material constructed by an aromatic diamine as claimed in claim 2, characterized in that: In the step 1, the molar ratio of methylamine hydrochloride to 3-aminomethylpyridine is 18:1 to 20:

1.

4. The method for preparing a DJ-type three-layer hybrid perovskite material constructed by an aromatic diamine as claimed in claim 2, characterized in that: The concentrations of methylamine hydrochloride and 3-aminomethylpyridine in step (1) are 0.068 g / mmol and 0.108 g / mmol respectively.

5. The method for preparing a DJ-type three-layer hybrid perovskite material constructed by an aromatic diamine as claimed in claim 2, characterized in that: The mass solubility of the hydrobromic acid solution described in step (1) is 48%, and the dosage is 30-35 mL.

6. The method for preparing a DJ-type three-layer hybrid perovskite material constructed by aromatic diamines as claimed in claim 2, characterized in that: The concentration of lead (II) acetate trihydrate described in step (1) is 0.379 g / mmol, and the amount used is 5 to 8 mmol.

7. The method for preparing a DJ-type three-layer hybrid perovskite material constructed by aromatic diamines as claimed in claim 2, characterized in that: The programmed cooling method described in step (2) is set to cool down by 0.5°C to 1°C every day, and the slow cooling time is 35 to 40 days.

8. The method for preparing a DJ-type three-layer hybrid perovskite material constructed by aromatic diamines as claimed in claim 2, characterized in that: The final temperature of the programmed cooling in step (2) is 45°C to 30°C.

9. The use of a DJ-type three-layer hybrid perovskite material constructed by an aromatic diamine as claimed in claim 1, characterized in that: Used to make X-ray detectors.